Two Erysiphe species associated with recent outbreak of soybean powdery mildew: Results of molecular phylogenetic analysis based on nuclear rDNA sequences - Takamatsu S. (2014)
Serious outbreaks of powdery mildew by a fungus belonging to the mitosporic genus Oidium subgenus Pseudoidium have been reported on soybean (Glycine max) in a wide area of eastern Asia since 1998. The taxonomic and phylogenetic placement of the causal fungus has not yet been determined because of lack of the perfect stage. We found ascomata having mycelioid appendages on a single leaf of soybean infested by powdery mildew. Molecular phylogenetic analysis was conducted based on a total of 14 sequences of the rDNA internal transcribed spacer (ITS) region from 13 soybean and wild soybean (Glycine soja) materials collected in Japan, Korea, Vietnam, and the United States, combined with 47 sequence data obtained from the DNA databases. It was revealed that two Erysiphe species were associated with the outbreak of soybean powdery mildew. There was 16% difference between the two species in genetic divergence of the ITS sequence. One species with perfect stage has an ITS sequence identical to that of Erysiphe glycines on Amphicarpaea and is identified as Erysiphe glycines based on the ITS sequence and morphology of ascomata. The second species, without the perfect stage, is likely to be Erysiphe diffusa (= Microsphaera diffusa), known as the fungus causing soybean powdery mildew in the United States, because the ITS sequences are identical to those from materials collected in the United States. However, we need materials having ascomata of E. diffusa to confirm the species name.